2020
DOI: 10.3390/ijerph17249419
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Health and Physical Activity Levels during the COVID-19 Pandemic: A Systematic Review

Abstract: The coronavirus disease (COVID-19) pandemic has been devastating in all senses, particularly psychologically. Physical activity (PA) is known to aid psychological well-being, and it is worth investigating whether PA has been a coping strategy during this pandemic. The objective of this literature review is to analyze the extent to which engaging in PA during the COVID-19 pandemic impacts psychological health in the adult population. The literature was searched in all databases from the EBSCOhost Research Datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

24
222
4
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 277 publications
(257 citation statements)
references
References 53 publications
(129 reference statements)
24
222
4
7
Order By: Relevance
“…The risk of probable MD associated with decreased visits to greenspace was lower in the group using greenspace for psychological or physical purposes than the group not using greenspace for these reasons. A potential reason for this finding could be increased indoor physical activities (likely at home), which would mitigate general stress and psychological distress from COVID-19 [12]. The risk of probable MD was higher in the group using greenspace for social interactions than the group not using greenspace for such reason, which differs from findings of a previous study suggesting no significant association between greenspace and social support in pre-pandemic periods in Spain [40].…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…The risk of probable MD associated with decreased visits to greenspace was lower in the group using greenspace for psychological or physical purposes than the group not using greenspace for these reasons. A potential reason for this finding could be increased indoor physical activities (likely at home), which would mitigate general stress and psychological distress from COVID-19 [12]. The risk of probable MD was higher in the group using greenspace for social interactions than the group not using greenspace for such reason, which differs from findings of a previous study suggesting no significant association between greenspace and social support in pre-pandemic periods in Spain [40].…”
Section: Discussioncontrasting
confidence: 88%
“…Pandemic mitigation measures such as physical/social distancing interventions, while intending to reduce virus transmission, may be detrimental to mental health and wellbeing, which are already hampered under public health and economic crisis conditions. A few articles suggested that the prolonged stay-at-home orders could lead to adverse mental health outcomes such as MD, GAD, and loneliness [9][10][11][12]. Increased prevalence of MD and GAD after the outbreak was reported in some countries including Canada, China, and Greece [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Overall, our findings suggest a higher need to focus educational campaigns on dietary advice during the COVID-19 pandemic in order to prevent dangerous dietary changes and to recover a more healthy diet pattern after quarantine periods. Physical activity promotion could also be an effective tool to partially counterbalance the negative impact of food intake modification [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, validation is required from medical professionals as to the program’s efficacy in the long-term treatment of childhood obesity, especially when it comes to maintaining healthy behaviors. On the other hand, the coronavirus disease 2019 pandemic (COVID-19) [ 42 , 43 , 44 ] has affected the population’s physical activity and mental health [ 45 ]. Therefore, it is necessary to study whether this type of active video games can help maintain a healthy physical activity and at the same time, help people’s mental health.…”
Section: Discussionmentioning
confidence: 99%